The skin on the move but cold adapted: Fundamental misconceptions in the laboratory and clinic - Terence J Ryan (Wolters Kluwer Medknow Publications, 2010)
The skin is constantly on the move and at a temperature below 37ºC. The epidermis is a factory, and its blood supply and lymphatic drainage, as well as adipose tissue, are much dependent on movement and influenced by cooling. Neither histopathology (still pictures) nor in vitro studies at 37ºC reflect the true picture. Recent publications neglect older literature exploring these issues.